2012
DOI: 10.1158/0008-5472.can-12-0388
|View full text |Cite
|
Sign up to set email alerts
|

The Nedd8-Activating Enzyme Inhibitor MLN4924 Induces Autophagy and Apoptosis to Suppress Liver Cancer Cell Growth

Abstract: Posttranslational neddylation of cullins in the Cullin-Ring E3 ligase (CRL) complexes is needed for proteolytic degradation of CRL substrates, whose accumulation induces cell-cycle arrest, apoptosis, and senescence. The Nedd8-activating enzyme (NAE) is critical for neddylation of CRL complexes and their growth-promoting function. Recently, the anticancer small molecule MLN4924 currently in phase I trials was determined to be an inhibitor of NAE that blocks cullin neddylation and inactivates CRL, triggering an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(220 citation statements)
references
References 51 publications
13
206
1
Order By: Relevance
“…However, the present findings are contradictory to these observations, as increased expression of p53 was observed in HepG2 cells expressing wild-type and functional p53, and in Huh7 cells carrying the mutated and inactivated p53 gene (23). The results of the current study suggested that HP could induce apoptosis in HCC cells regardless of the p53 status.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the present findings are contradictory to these observations, as increased expression of p53 was observed in HepG2 cells expressing wild-type and functional p53, and in Huh7 cells carrying the mutated and inactivated p53 gene (23). The results of the current study suggested that HP could induce apoptosis in HCC cells regardless of the p53 status.…”
Section: Discussioncontrasting
confidence: 99%
“…Stabilization/induction of REDD1 was induced upon MLN4924 treatment in multiple myeloma and siRNA-mediated knockdown was shown to alleviate the cytotoxicity of MLN4924 (Gu et al 2014). Furthermore, MLN4924-mediated mTOR inhibition was shown to trigger pro-survival autophagy in liver cancer cells and simultaneous inhibition of autophagic responses enhances cytotoxic effects (Luo et al 2012). This is consistent with a previous report with knockdown of RING finger protein Rbx1 in the CRL complex, in which protective autophagic responses were also induced .…”
Section: Skp2supporting
confidence: 90%
“…In contrast to the tumourpromoting role of Smurf1, Smurf2 has been suggested to function as a tumour suppressor gene since ablation of Smurf2 in mice resulted in increased susceptibility to various types of cancers in aged mice 61 . We noted that the NAE inhibitor MLN4924 has been recently identified as a novel approach to the treatment of acute myeloid leukaemia, head and neck cancer and liver cancer [62][63][64] . In addition, MLN4924 was demonstrated to inhibit tumour growth in lung cancer xenografts 65 .…”
Section: Discussionmentioning
confidence: 99%